(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
India’s West Asia strategy talk has customarily rotated around its energy reliance, security and the government assistance of the 7 million Indians living in the locale. As of late, especially since the happening to the Bharatiya Janata Party (BJP) to control in 2014, the issues of counterterrorism, security, guards participation and non-oil exchange have acquired in significance. This subjective shift is to some extent directed and upheld by both practicality and the philosophical contrasts that the BJP and its archetype, the Bharatiya Jana Sangh (BJS), had been keeping up with against the West Asia strategy of the previous state run administrations drove by the Congress party. Through clarifying the philosophical points of view of the Indian National Congress (INC) and the BJP, this article contends that the changing worldwide and West Asian scene, the combination of Chinese impact in and around India’s property and sea limits, the precariousness in the energy market and the uncertainty of the Arab uprising–hit West Asian governments have given the BJP government an advantageous chance to reconsider and reorient India’s relations with West Asia. While philosophical determinants rule the public talk, as the BJP’s top initiative expounds in the public area, the arrangement decisions made are not generally on top of these. State leader Narendra Modi has frequently favored the practical to the philosophical, and this he has done over the assumptions for his party and allies.